Effects of pitch size and skill level on tactical behaviours of association football players during small-sided and conditioned games - Silva, P.; Aguiar, P.; Duarte, R.; Davids, K.; Araújo, D.; Garganta, J. (International Journal of Sports Science and Coaching, 2014)
In Association Football, the study of variability in players' movement trajectories during performance can provide insights on tactical behaviours. This study aimed to analyse the movement variability present in: i) the players' actions zones and ii), distances travelled over time, considered as a player's positional spatial reference. Additionally, we investigated whether the movement variability characteristics of players from different skill levels varied. Two groups of U-17 yrs players of different performance levels (national and regional) performed in three small-sided games with varying pitch dimensions (small, intermediate and large). Linear and non-linear analyses were used to capture the magnitude and structure of their movement variability. Results showed that increases in pitch size resulted in more restricted action zones and higher distance values from personal spatial positional references for both groups. National-level players were more sensitive to pitch modifications and displayed more variability than regional-level players in the small and intermediate pitches. These findings advance understanding about individual tactical behaviours in Association Football and have implications for training design, using pitch size manipulation.